MAPPING THE TEACHERS' PSYCHOLOGICAL COMPETENCIES: A BIBLIOMETRIC ANALYSIS OF COGNITIVE AND SOCIO-EMOTIONAL DOMAINS - Selvi Sumardin; Dian Kusuma Hapsari (Faculty of Psychology, Diponegoro University, 2025)
The increasing demands of inclusive education have revealed critical gaps in pre-service teachers' psychological preparedness, necessitating a systematic investigation of core competency domains and their development trends. This study aims to address this gap by systematically analyzing 42 years (1983-2025) of global research on pre-service teachers' psychological competencies. Using bibliometric methods, we examined 911 Scopus-indexed publications with VOSviewer for co-citation and keyword co-occurrence analysis. This study identified four pivotal competency areas: (1) Emotional Regulation and Well-being (Clusters 2 & 5), highlighting the need for stress management and resilience training to address burnout risks; (2) Self-Efficacy and Professional Identity (Clusters 2 & 6), emphasizing cultural competence and reflective practices for diverse classrooms; (3) Cognitive-Metacognitive Strategies (Cluster 4), where self-regulated learning and adaptive teaching significantly enhance instructional outcomes; and (4) Motivational Competencies (Cluster 7), focusing on intrinsic motivation and autonomy-supportive techniques to sustain engagement. These findings provide a roadmap for integrating these four competency domains into teacher training programs, offering actionable insights for developing psychologically resilient educators equipped for inclusive education demands.